Le développement de la compétence interculturelle dans l’enseignement du français professionnel à l’université - Ganea, Alina (Taikomoji kalbotyra, 2018)
Cette étude interpelle une problématique incontournable tenant à l’enseignement à l’université, à savoir l’adaptation continue aux exigences du marché du travail, ce qui se traduit au niveau des contenus par une mise en concordance des objectifs d’enseignement avec les compétences professionnelles requises. Au niveau de l’enseignement d’une langue étrangère à des fins professionnelles, cette mise en concordance implique, entre autres, l’intégration de la dimension interculturelle dans les contenus dispensés afin de munir l’étudiant des compétences nécessaires pour qu’il/elle puisse (inter)agir dans le contexte multiculturel actuel du marché du travail. Dans ce contexte, cette étude propose, dans un premier temps, un retour théorique sur les concepts culture et interculturel envisagés comme des balises significatives dans l’enseignement actuel des langues étrangères et qui précisent, par les compétences spécifiques à atteindre, les nouvelles exigences auxquelles l’enseignement d’une langue étrangère doit satisfaire. Notre recherche se poursuit par un retour sur les spécificités de l’enseignement d’une langue étrangère à des fins professionnelles et fournira une proposition concrète d’alignement des contenus enseignés dans le cours Langues modernes (français) pour la filière de médecine de notre université aux objectifs de la compétence interculturelle. Une proposition de programme contenant des activités visant l’interculturel articulées autour des contenus initialement proposés pour cette spécialisation sera avancée. Developing intercultural competence in teaching French for professional purposes at university Our study investigates an essential problem related to university teaching, namely continuous adaptation to the labour market standards and requirements, which at the curriculum level involves a correlation between learning objectives and competency profile requested and expected in the professional world. With respect to foreign language teaching for professional purposes, this correlation implies, among other things, the integration of intercultural dimension in the contents taught in order to provide the student with necessary skills and enabling him/her able to efficiently (inter)act in today’s multicultural labour market, and finally meet the needs of contemporary world. In this context, our research firstly offers a theoretical approach to the concepts of culture and interculturel, which are envisaged as landmarks in today’s foreign language teaching philosophy and which specify, through their specific objectives to be achieved, new standards that foreign language teaching must comply with. Our study also offers a theoretical framework to the particularities of foreign language teaching for professional purposes. This enables us to reformulate the initial objectives associated to foreign language for professional purposes by integrating the objectives related to the development of intercultural competence. Finally, this study also proposes a concrete course content of medical French based on the course already delivered to the students studying medicine in Dunarea de Jos University of Galati. The course has been remodelled so as to meet the objectives of intercultural competence. In doing so, we firstly analysed the topics included in the course content with respect to aspects related to culture or intercultural communication, and afterwards we provided a list of cultural- and intercultural communication-oriented topics that could be articulated around the already proposed content of a French course for medicine. This proposal is also accompanied by a series of methodological recommendations that should be taken into consideration prior to designing a course for medical French. Key words: French for professional purposes; culture; intercultural; competence; teaching and learning.